Analisis Perilaku Organisasi Pada Imlpementasi Clinical Pathway Pasien Dengan ST-Elevasi Miokard Infark (STEMI) Di RSUP Dr. Kariadi Semarang - Muhammad Mukhlis Sujudi; Sutopo Patria Jati; Farid Agushybana (Jurnal Manajemen Kesehatan Indonesia, 2022)
Implementation of CP (clinical pathway) as the main requirement for quality control and hospital costs is important in providing services. CP implementation is influenced by many factors. As many as 90% of filling in CP was not policies and SOPs based. This study aims to determine organizational behavior towards the implementation of CP in patients with STEMI at dr. Kariadi Semarang. This research was a qualitative descriptive study. Collecting data through in-depth interviews and observations. Interviews were conducted to 6 informants who were selected using purposive sampling technique. Data were analyzed descriptively and presented in narrative form. The results showed that the implementation of CP in dr. Kariadi Semarang has been carried out since 2012 and has undergone adjustments to the KARS standard in the Guidelines for the Preparation of Clinical Practice Guidelines and Clinical Pathways in Integrated Care according to the 2012 Hospital Accreditation Standard Edition I. The hospital director assigned the Director's Decree No. HK.00.01/I.IV/600/2016, No. KP.08.02/I.IV/434/2016, No. HK.00.01/I.IV/432/2016 and SOPs to support CP implementation. The adequacy of the workforce needs to be reconsidered. Compliance with CP implementation has not been maximized. Barriers to the implementation of CP was limited human resources, CP has not been integrated with RME in real time, recapitulation of CP was retrospective, evaluation of compliance by yanmed has not been audited by the Medical Committee on a regular basis, PPA compliance, consistency of medical record writing, and patient condition. Monitoring, evaluation and communication need to be developed to optimize the implementation of CP.